2021
DOI: 10.1111/jace.17954
|View full text |Cite
|
Sign up to set email alerts
|

Nucleating role of P2O5 in nepheline‐based transparent glass‐ceramics

Abstract: The nepheline-based transparent glass-ceramics are promising candidates for cover glass applications in electronic displays owing to their superior mechanical properties (than glasses) and ability to be chemically strengthened. However, our poor understanding about the kinetic and thermodynamic drivers controlling their crystallization processes usually results in their opacification and development of large internal stresses. The present work focuses on the development of nepheline-based nanocrystalline trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Similarly, Ahmad et al 38 . found the nepheline formation during the sintering process from 900°C to 1200°C of kaolin‐based geopolymer, where the characteristic peaks of nepheline became narrower and intensified as the temperature increased 22 . Padilla et al.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Similarly, Ahmad et al 38 . found the nepheline formation during the sintering process from 900°C to 1200°C of kaolin‐based geopolymer, where the characteristic peaks of nepheline became narrower and intensified as the temperature increased 22 . Padilla et al.…”
Section: Resultsmentioning
confidence: 88%
“…The characteristic peaks at 13.9 • and 24.26 • attributed to sodalite only exist in the XRD patterns obtained at 80 • C and 600 • C, which are replaced by the new peaks at 21.199 • and 35.077 • (PDF #52-1342) of nepheline (NaAlSiO 4 ) first appearing at 800 • C. It is worth noting that, for different Si/Al ratios, XRD patterns display high consistency in the number of nepheline peaks over the temperature range from 800 • C to 1200 • C. Similarly, Ahmad et al 38 found the nepheline formation during the sintering process from 900 • C to 1200 • C of kaolin-based geopolymer, where the characteristic peaks of nepheline became narrower and intensified as the temperature increased. 22 Padilla et al reported that the conversion from sodalite (a cubic crystal) to pure nepheline (a hexagonal crystal) took place in the 800 • C-900 • C interval. 29 Phase transition from kaolinite to sodalite and further to nepheline is unified and the main composition of sintered geopolymers with different Si/Al ratios is similar at the same temperature, except for the increasing intensity of quartz due to the additional silica.…”
Section: Phase Transition and Microstructure Evolution Of Geopolymer ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Li et al 122 . examined the nucleating role of P 2 O 5 in nepheline (NaAlSiO 4 )‐based transparent glass–ceramics with the composition of 21Na 2 O–5.7K 2 O–4.7P 2 O 5 –19.4Al 2 O 3 –49.2SiO 2 (mol%) with [Na 2 O+K 2 O]/[Al 2 O 3 ] = 1.37 and proposed that Na 3 PO 4 nanocrystals formed initially promote the volume crystallization of nepheline K 0.12 Na 0.87 Al 0.99 Si 1.01 O 4 nanocrystals.…”
Section: Structure and Crystallization Of Li2o–sio2‐basd Glassesmentioning
confidence: 99%